Six Stroke Engine - Rajesh Holkar; Vishal Satish Jagadale (International Journal of Innovations in Engineering Research and Technology, 2021)
The increasing demands for low emissions and low fuel consumption in modern combustion engines requires improved methods for combustion process. The Beare Head is a new type of six-stroke engine head design known as the “Beare Head” after its designer, Malcolm Beare. The Beare Head uses a piston and ports very much like a two stroke engine to replace the overhead valve system that is found in four stroke engines today. The four-stroke block, piston and crankshaft remain unaltered. This combination of two stroke and four-stroke technology has given the technology its name the “six stroke engine”. Six Stroke engine, the name itself indicates a cycle of six strokes out of which two are useful power strokes. According to its mechanical design, the six-stroke engine with external and internal combustion and double flow is similar to the actual internal reciprocating combustion engine.